Use of government assisted financing by SMEs: an empirical examination of Canadian SMEs using the financial growth cycle - Osakwe, C.; Dhaliwal, S.; Jagoda, K. (International Journal of Accounting & Business Finance, 2023)
This study examines Small and Mid-sized Enterprises (SMEs) through the lens of the financial growth cycle, which emphasizes that an entity’s financing options change as they change in size, age, and informational transparency. For this study, we examined SMEs in the city of Corner Brook, the second largest city in the province of Newfoundland & Labrador, analyzing their sources of capital while specifically focusing on two main attributes, size and age. Utilizing the financial growth cycle model, we examined how efficiently SME financing needs are being met through the various options available to them as they grow in size and age. We discuss in particular, findings related to government assisted financing, concluding that as SMEs grows older, they are increasingly likely to opt for federally funded financing as a source of capital. In this study, we sampled SMEs in one city (Corner Brook) to empirically test the financial growth cycle paradigm. The paper investigates the role that government sponsored financing plays in overcoming the information opacity problem of SMEs at different stages of the growth cycle. The study observes that government sponsored financing appears to play an important role in SME financing. The finding suggests that firms should consider accessing sources of government financing even at an early stage in the financial growth cycle.
Keywords: Small and Mid-sized Enterprise; Financing; Financial Growth Cycle; Canada JEL Code:M131